THE LEGITIMACY OF THE USE OF ARMED FORCE A COMPARATIVE STUDY BETWEEN ISLAM AND INTERNATIONAL LAW (World Bulletin of Management and Law, 2022)
The research focuses on the legality of the use of military force in public international law and Islamic Sharia and its importance in determining the cases of collective legitimate defense and the development of explicit legal instructions in the Charter of the United Nations that enable states to collective legitimate defense in cases of a coup against legitimacy or facing aggression by another state